A randomized controlled trial of everolimus for neurocognitive symptoms in PTEN hamartoma tumor syndrome. Issue 20 (20th May 2022) - Srivastava, Siddharth; Jo, Booil; Zhang, Bo; Frazier, Thomas; Gallagher, Anne Snow; Peck, Fleming; Levin, April R; Mondal, Sangeeta; Li, Zetan; Filip-Dhima, Rajna; Geisel, Gregory; Dies, Kira A; et al.
Abstract: PTEN hamartoma tumor syndrome (PHTS) is a complex neurodevelopmental disorder characterized by mechanistic target of rapamycin (mTOR) overactivity. Limited data suggest that mTOR inhibitors may be therapeutic. No placebo-controlled studies have examined mTOR inhibition on cognition and behavior in humans with PHTS with/without autism. We conducted a 6-month phase II, randomized, double-blinded, placebo-controlled trial to examine the safety profile and efficacy of everolimus (4.5 mg/m 2 ) in individuals (5–45 years) with PHTS. We measured several cognitive and behavioral outcomes, and electroencephalography (EEG) biomarkers. The primary endpoint was a neurocognitive composite derived from Stanford Binet-5 (SB-5) nonverbal working memory score, SB-5 verbal working memory, Conners' Continuous Performance Test hit reaction time and Purdue Pegboard Test score. Forty-six participants underwent 1:1 randomization: n  = 24 (everolimus) and n  = 22 (placebo). Gastrointestinal adverse events were more common in the everolimus group ( P  < 0.001). Changes in the primary endpoint between groups from baseline to Month 6 were not apparent (Cohen's d = −0.10, P  = 0.518). However, several measures were associated with modest effect sizes (≥0.2) in the direction of improvement, including measures of nonverbal IQ, verbal learning, autism symptoms, motor skills, adaptive behavior and global improvement. There was a significant difference in EEG central alpha power ( P  = 0.049) and central beta power ( P  = 0.039) 6 months after everolimus treatment. Everolimus is well tolerated in PHTS; adverse events were similar to previous reports. The primary efficacy endpoint did not reveal improvement. Several secondary efficacy endpoints moved in the direction of improvement. EEG measurements indicate target engagement following 6 months of daily oral everolimus. Trial Registration Information: ClinicalTrials.gov NCT02991807 Classification of Evidence: I.